Femtosecond fiber Bragg grating fabrication with adaptive optics aberration compensation - Salter, P; Woolley, M; Morris, S; Booth, M; Fells, J (Optical Society of America, 2018)
We present fiber Bragg gratings (FBGs) fabricated using adaptive optics aberration compensation for the first time to the best of our knowledge. The FBGs are fabricated with a femtosecond laser by the point-by-point method using an air-based objective lens, removing the requirement for immersion oil or ferrules. We demonstrate a general phase correction strategy that can be used for accurate fabrication at any point in the fiber cross-section. We also demonstrate a beam-shaping approach that nullifies the aberration when focused inside a central fiber core. Both strategies give results which are in excellent agreement with coupled-mode theory. An extremely low wavelength polarization sensitivity of 4 pm is reported.